TRANSIT OF POWER IN CHAD UNDER A CROSS-BORDER ENVIRONMENT - Poble, Dmytro; Kanevskiy, Mariia (SWorld-Ger Conference proceedings, 2024)
The theses are dedicated to studying the problem of power transfer using the example of an African country, especially taking into account the factors that influence the so-called transit of power under a cross-border environment. The relevance of this st